القيادة بين المنظور الإسلامي والأدب المعاصر في علوم الإدارة والقيادة: (Leadership between the Islamic Perspective and Contemporary Literature of Management and Leadership Sciences) - Ali Shaladi, Abdul Rahman Abu Bakr; Lubis, Asmuliadi; Kamri, Nor’Azzah (Online Journal of Research in Islamic Studies, 2024)
This paper employs an inductive methodology to elucidate the essence of leadership from the Islamic perspective, highlighting distinctive characteristics and traits of Islamic leaders. The study also presents and clarifies the five theories of leadership and their three styles from the standpoint of contemporary thought of management and leadership sciences. Additionally, it provides an overview of leadership in the educational field, The paper concludes by asserting that Islamic philosophy offers a unique model of leadership that differs from other theories. Islamic leadership is exemplified through the life, actions, and various situations of the Prophet, emphasizing its significant importance, great trust, and profound responsibility. Islamic philosophy mandates that Muslims choose their leader through consultation (shura), urging them not to leave the leadership position vacant for an extended period, as it may lead to significant corruption. Simultaneously, it prohibits individuals from seeking leadership or imposing themselves on the Islamic community due to the distinctive style of Islamic leadership, in contrast to other models in contemporary organizations and governments. Islamic leadership is characterized by moderation and balance, avoiding authoritarianism, rigidity, leniency, control, or absolute democracy. Unlike other worldly theories and philosophies, it is a divine philosophy distinguished by justice, wisdom, stewardship of the Earth, and responsibility towards God and creation.